2023
DOI: 10.6023/cjoc202212021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Bioactivities of Novel Pyrazole Oxime Derivatives Containing 1,3,4-Oxadiazole Group

Abstract: In order to explore new pyrazole oxime compounds possessing satisfactory bioactivities, sixteen pyrazole oxime derivatives containing 1,3,4-oxadiazole group were prepared with fenpyroximate selected as lead structure. Their insecticidal activities were determined. Preliminary bioassay demonstrated that all the target compounds displayed 100% insecticidal activities towards Mythimna separata at 500 μg/mL, of which 5 target compounds possessed 80%~100% insecticidal activities against Mythimna separata at 100 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recently, Wang et al found that oxazole-containing pyrazole oxime ether derivative A ( Figure 1 ) had a broad spectrum of insecticidal and fungicidal properties [ 28 ]. Sun et al reported pyrazole oxime ether B ( Figure 1 ) with an aryloxy-linked 1,3,4-oxadiazole moiety displaying satisfactory insecticidal effects [ 29 ]. This greatly promoted the development of bioactive pyrazole oxime ether molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al found that oxazole-containing pyrazole oxime ether derivative A ( Figure 1 ) had a broad spectrum of insecticidal and fungicidal properties [ 28 ]. Sun et al reported pyrazole oxime ether B ( Figure 1 ) with an aryloxy-linked 1,3,4-oxadiazole moiety displaying satisfactory insecticidal effects [ 29 ]. This greatly promoted the development of bioactive pyrazole oxime ether molecules.…”
Section: Introductionmentioning
confidence: 99%